Застосування генеративного штучного інтелекту в дистанційному навчанні - Волобуєва, Д. С.; Водяницький, Д. В. (ХНУРЕ, 2025)
The forced transition to distance learning under wartime conditions ensured the continuity of the educational process in Ukraine. However, the use of electronic textbooks alone did not make education fully digital, nor could various video conferencing tools completely replace in-person interaction. One promising approach to enhancing the effectiveness of distance learning is the application of generative artificial intelligence methods. This technology enables the creation of a personalized learning environment where students can effectively acquire knowledge, access additional information, and receive explanations even in asynchronous learning settings.
Keywords: дистанційне навчання